PENDAMPINGAN PEMASARAN UMKM UNTUK MENINGKATKAN DAYA SAING MELALUI PEMBUATAN MEDIA SOSIAL DI UMKM ABON RIZKY - Supiani Supiani; Tresna Nurhidayah; Adi Rosadi (Jurnal Ekonomi dan Bisnis, 2025)
The Abon Rizky MSME in Cimangkok Village, Sukalarang Subdistrict, Sukabumi Regency, is facing serious marketing challenges, with approximately 70% of business owners struggling to utilize social media, and more than 60% still relying on traditional methods. The Community Service Program (PKM) aims to improve digital marketing skills through training and mentoring. The methods applied involve interactive sessions on the use of social media, content creation, and practical marketing strategies. The results of the program show a significant increase in the knowledge and skills of the Abon Rizky MSMEs, as well as a rise in product sales after the training. With proper support, the Abon Rizky MSME in Cimangkok Village can improve its competitiveness in the market. This program not only helps Abon Rizky MSMEs survive but also contributes to local economic growth, creates job opportunities, and strengthens community welfare. The new skills acquired become an important asset for business sustainability.